Herbert Spencer, Sociological Theory, and the Professions - Offer, John (Frontiers in Sociology, 2019)
This article presents new insights into Spencer’s theoretical sociology as he applied it to the professions and professional institutions, which he discussed extensively, particularly in his Principles of Sociology. The first part of this article notes the main conceptual insights which he established and aligns them within the wider context of a re-reading of Spencer’s sociology. Particular attention is paid to the 'social organism' and the spontaneous cooperation of social individuals in society (with each possessing 'social self-consciousness'). This part also reappraises Spencer’s account of the emergence of ‘professionals’ and their distinctive ‘cunning, skill, and acquaintance with the nature of things’, which professionals have brought to bear on what has been experienced in the ordinary social lives of people as the complexity or the unfamiliar in the world. The subsequent discussion focuses on, first, a retrieval of Spencer’s theoretical stance on the activities of the professions, and on work and conditions in general, and, second, on reviewing some of the major resonances which his work has with practical problems and the associated theoretical issues concerning the sociological understanding of professional/service-user interaction in social life today.